Episode depicting the Acharya’s miraculous powers in saving lives - Temples of India Project Team (Jio Institute, 2024)
The sixth oval painting (in clockwise order) is in the lower/outer circle in the ceiling of the mandapa (pillared hall) of the Bhandasar Temple. Here is another episode depicting the acharya’s (those who impart knowledge) miraculous powers in saving lives. Two disciples are shown seeking help from the acharya, who is then depicted granting them the necessary assistance. The inscription reads, ‘Shri Jinadatta Suriji anas ro ji vayo.’